Review of implantable-based wireless body area network metrics issues - Majdoubah, Rawan Al; Eljaafreh, Yousef (International Journal of Electrical and Computer Engineering (IJECE), 2025)
Recent developments in wireless communications, low-power integrated circuits, and biological physiological sensors have led to a new generation of wireless sensor networks. Body area networks are an interdisciplinary field that allows for real-time updates of medical records via the internet and continuous, affordable health monitoring. Several intelligent physiological sensors can be easily integrated into a flexible wireless body area network for implanted use, supporting early disease detection or computer-assisted rehabilitation. This field relies on the feasibility of small, easily implanted biosensors that do not impede daily activities. The body's implanted sensors record various physiological changes to monitor the patient's status no matter where they are. Nonetheless, because they handle health data, these networks ought to use benchmarking criteria to ensure high levels of service quality. Network routing protocols, wireless technologies, quality of service, privacy and security, energy efficiency, and performance are among the challenges being focused on to better satisfy its expectations. This review aims to comprehensively compare implantable wireless body area network metrics issues, seeking to generate a consistent and understandable overview. This study also attempts to address the gaps and provides a current assessment of the metrics concerning a wireless body area network used in healthcare services.